Perspectives of carers on medication management in dementia: lessons from collaboratively developing a research proposal - Fiona Poland; Sarah Mapes; Hilary Pinnock; Cornelius Katona; Susanne Lillelund Sørensen; Chris Fox; Ian Maidment (2014)
The need for carers to manage medication-related problems for people with dementia living in the community raises dilemmas, which can be identified by carers and people with dementia as key issues for developing carer-relevant research projects. A research planning Public Patient Involvement (PPI) workshop using adapted focus group methodology was held at the Alzheimer’s Society’s national office, involving carers of people with dementia who were current members of the Alzheimer’s Society Research Network (ASRN) in dialogue with health professionals aimed to identify key issues in relation to medication management in dementia from the carer viewpoint. The group was facilitated by a specialist mental health pharmacist, using a topic guide developed systematically with carers, health professionals and researchers. Audio-recordings and field notes were made at the time and were transcribed and analysed thematically. The participants included nine carers in addition to academics, clinicians, and staff from DeNDRoN (Dementias and Neurodegenerative Diseases Research Network) and the Alzheimer’s Society. Significant themes, for carers, which emerged from the workshop were related to: (1) medication usage and administration practicalities, (2) communication barriers and facilitators, (3) bearing and sharing responsibility and (4) weighing up medication risks and benefits. These can form the basis for more in-depth qualitative research involving a broader, more diverse sample. The supported discussion enabled carer voices and perspectives to be expressed and to be linked to the process of identifying problems in medications management as directly experienced by carers. This was used to inform an agenda for research proposals which would be meaningful for carers and people with dementia.